Cloning and expression of African swine fever virus K205R and B602L genes inf. COLI - A. V. Scherbakov; A. S. Yakovleva; A. M. Timina; M. R. Yakupov (Ветеринария сегодня)
A molecular cloning of African swine fever virus k205r and b602l genes in £ coli was carried out. The expression and purification conditions ensuring high yield of recombinant proteins were optimized. Dissolved recombinant proteins were purified by metal-chelate affinity chromatography using Ni-NTA-agarose («Qiagen»). Recombinant antigens are biologically safe, easier to prepare and ensure higher ELISA specificity. The purified protein yield from 100 ml off. coli culture was 1,5 mg for pK205R and 2 mg for pB602L.